The semantic map of when and its typological parallels - Haug, Dag; Pedrazzini, Nilo (Frontiers in Communication, 2023)
In this paper, we explore the semantic map of the English temporal connective when and its parallels in more than 1,000 languages drawn from a parallel corpus of New Testament translations. We show that there is robust evidence for a cross-linguistic distinction between universal and existential when. We also see tentative evidence that innovation in this area involves recruiting new items for universal when which gradually can take over the existential usage. Another possible distinction that we see is between serialized events, which tend to be expressed with non-lexicalized constructions and framing/backgrounding constructions, which favour an explicit subordinator.